Developing STEAM-Based Digital Mathematics Teaching Materials to Enhance Creativity - Mutmainnah Mutmainnah; Sitti Fitriani Saleh; Abdul Halim Abdullah; Jumrah Jumrah; Nurwanda Nurwanda; Ahmadhani Ahmadhani (Universitas Pendidikan Mandalika, 2026)
This study was motivated by the low level of creativity among elementary school students in mathematics learning, which is still largely dominated by conventional methods and rote memorization. The aim of this study was to develop digital mathematics teaching materials based on the STEAM approach (Science, Technology, Engineering, Arts, and Mathematics) to enhance students' creativity. This study employed a Research and Development (R&D) design using the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation. The analysis stage was conducted through classroom observations and interviews to identify learning needs. The developed product was validated by education experts, subject-matter experts, and STEAM experts, and was subsequently tested for practicality by teachers and students, as well as for effectiveness through the implementation of STEAM-based digital mathematics teaching materials at Lab School SD Unismuh Makassar. The results of the needs analysis indicated a demand for more interactive learning strategies and media that could help students understand concepts visually and contextually. The design of STEAM-based digital mathematics teaching materials in elementary schools is not only oriented toward academic outcomes, but also toward shaping students' character, creativity, and 21st-century skills. The evaluation results from the three validators (education expert, subject-matter expert, and STEAM expert) showed an average score of 3.28 or 85.56%, which falls into the very valid category. The practicality test involving teachers and students yielded an average score of 3.3 or 82.5%, which falls within the interval of 70% ≤ P < 85% and is categorized as practical. This indicates that the teaching materials were considered easy to use, clear, and relevant to students' learning needs. The implementation results showed a significant improvement. The analysis demonstrated that STEAM-based digital mathematics teaching materials contributed to an increase in students' creativity. Descriptively, the mean creativity score increased from 2,799 (pretest) to 3,399 (posttest). This improvement was also supported by a class N-gain score of 0.500 (moderate category), indicating a meaningful improvement in learning from an educational perspective. Furthermore, the paired-sample difference test revealed a significant difference between the pretest and posttest results (Sig. 2-tailed = 0.002 < 0.05), confirming that the use of STEAM-based digital teaching materials had a significant effect on improving students' creativity.